2014
DOI: 10.1080/13825585.2014.915918
|View full text |Cite|
|
Sign up to set email alerts
|

Repetition-lag training to improve recollection memory in older people with amnestic mild cognitive impairment. A randomized controlled trial

Abstract: The results of a randomized controlled trial of repetition-lag training in older adults with amnestic mild cognitive impairment (aMCI) are reported. A modified repetition-lag training procedure with extended encoding time and strategy choice was used. The training required discriminating studied words from non-studied lures that were repeated at varying intervals during the test phase. Participants were assessed pre/post using untrained measures of cognition and self-report questionnaires. Primary outcome meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 31 publications
1
53
0
Order By: Relevance
“… Fiatarone Singh et al ( 2014 ) RCT, double-blind, active control n = 100 Tx n = 24 Cntl = 27 Age: = 70.1 s = 6.7 • 4–45 min exercises (initial/ group setting); then 45 min sessions, 2 days per week for 24 weeks • CT computer-based multicomponent and multi-domain compensatory training in memory, executive functions, attention, and speed of information processing (COGPACK) ADAS-Cog; MMSE; GP-Cog; CDR; Matrices, Similarities, TMT A & B, LM Iⅈ BVMT-R; SDMT; Semantic Fluency, COWAT, MARS-MF • ADAS-Cog scores: No differences between CT and sham cognitive training • CT group demonstrated modest non-significant changes as compared to controls across cognitive domains • CT group maintained memory ability, no significant improvement or decline • CT reported to attenuate decline in memory • There was no significant change in cognitive outcomes between CT and sham training in global cognition, executive functions, memory, or speed 2.035 7. Finn and McDonald ( 2011 ) RCT, single-blind, inactive control n = 16 (MCI-SD/MD) Tx = 8 Cntl = 8 Age: Tx: = 69.00 s = 7.69 Cntl; = 76.38 s = 6.47 • 30 sessions, 11.43 weeks/ completion • Computer-based restorative training program involving attention, processing speed, visual memory, cognitive control (LUMOSITY) 1° - CANTAB, RVP A, PAL, IED 2° - MFQ, DASS-21 • Significant CANTAB tests: main effect of group - attentional set shifting, visual learning, visual working memory F (2, 14) = 0.35, 1.17, and 3.55, respectively • ↑ in visual sustained attention treatment (pre/ post difference RVPA’ = .03) compared with waitlist ctrl (pre/ post difference RVPA’ = − .06) • No significant data on self-reported memory functioning and perceptions of control over memory • ↑ in performance on visual sustained attention compared to waitlist controls • No significant changes on other primary outcome measures • MCI patients can ↑ performance significantly when given repeated practice on computerized cognitive exercises but study did not translate to secondary measures −1.401 8. Finn and McDonald ( 2015 ) RCT, inactive control n = 24 (aMCI) Tx = 12 Cntl = 12 Age: Tx: = 72.83 s = 5.7 Cntl; = 75.08 s = 7.5 • 6 sessions over several weeks (plus one practice session).…”
Section: Resultsmentioning
confidence: 99%
“… Fiatarone Singh et al ( 2014 ) RCT, double-blind, active control n = 100 Tx n = 24 Cntl = 27 Age: = 70.1 s = 6.7 • 4–45 min exercises (initial/ group setting); then 45 min sessions, 2 days per week for 24 weeks • CT computer-based multicomponent and multi-domain compensatory training in memory, executive functions, attention, and speed of information processing (COGPACK) ADAS-Cog; MMSE; GP-Cog; CDR; Matrices, Similarities, TMT A & B, LM Iⅈ BVMT-R; SDMT; Semantic Fluency, COWAT, MARS-MF • ADAS-Cog scores: No differences between CT and sham cognitive training • CT group demonstrated modest non-significant changes as compared to controls across cognitive domains • CT group maintained memory ability, no significant improvement or decline • CT reported to attenuate decline in memory • There was no significant change in cognitive outcomes between CT and sham training in global cognition, executive functions, memory, or speed 2.035 7. Finn and McDonald ( 2011 ) RCT, single-blind, inactive control n = 16 (MCI-SD/MD) Tx = 8 Cntl = 8 Age: Tx: = 69.00 s = 7.69 Cntl; = 76.38 s = 6.47 • 30 sessions, 11.43 weeks/ completion • Computer-based restorative training program involving attention, processing speed, visual memory, cognitive control (LUMOSITY) 1° - CANTAB, RVP A, PAL, IED 2° - MFQ, DASS-21 • Significant CANTAB tests: main effect of group - attentional set shifting, visual learning, visual working memory F (2, 14) = 0.35, 1.17, and 3.55, respectively • ↑ in visual sustained attention treatment (pre/ post difference RVPA’ = .03) compared with waitlist ctrl (pre/ post difference RVPA’ = − .06) • No significant data on self-reported memory functioning and perceptions of control over memory • ↑ in performance on visual sustained attention compared to waitlist controls • No significant changes on other primary outcome measures • MCI patients can ↑ performance significantly when given repeated practice on computerized cognitive exercises but study did not translate to secondary measures −1.401 8. Finn and McDonald ( 2015 ) RCT, inactive control n = 24 (aMCI) Tx = 12 Cntl = 12 Age: Tx: = 72.83 s = 5.7 Cntl; = 75.08 s = 7.5 • 6 sessions over several weeks (plus one practice session).…”
Section: Resultsmentioning
confidence: 99%
“…Hours of contact could be calculated in 12 of the 14 studies (excludes Finn and McDonald 2015; Rojas et al 2013), ranging from 4.5 (Jean et al 2010b) to 156 h (Lam et al 2015). Excluding Lam et al as an outlier, studies averaged 15.5 h of intervention (SD = 10.1).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the therapist-based intervention studies (11/14) utilized a group setting for their intervention, only three studies (Finn and McDonald 2015; Greenaway et al 2013; Jean et al 2010b) had solely individual sessions. Nakatsuka et al (2015) had both group and in-home individual sessions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…107,108 Likewise, trials of memory recollection training have shown limited generalization. 109,110 These latter efforts indicate that restorative approaches, attempting to retrain specific cognitive processes, may be less effective cognitive rehabilitation approaches than compensatory approaches such as memory strategy training.…”
Section: Treatment Of MCImentioning
confidence: 99%